1981
DOI: 10.1139/y81-079
|View full text |Cite
|
Sign up to set email alerts
|

Renin substrate in rat mesenteric artery

Abstract: The concentration of renin substrate (RS) was measured in rat mesenteric artery tissue. The concentration of this substrate both in arterial tissue and in plasma was markedly higher in rats 1 day after bilateral nephrectomy than in sham-operated controls, the percentage difference being higher in plasma than in arterial RS. Conversely, the decrease apparently induced 3 days after adrenalectomy (i.e., the difference in RS concentration from sham-operated rats) was greater in arterial tissue than in plasma. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

1986
1986
1996
1996

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…Studies of vascular angiotensinogen and reninlike activity have been unable to exclude plasma as their source (46,47). Re et al (48) and Lilly et al (49) have provided evidence for the synthesis of renin by vascular smooth muscle and endothelial cells in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…Studies of vascular angiotensinogen and reninlike activity have been unable to exclude plasma as their source (46,47). Re et al (48) and Lilly et al (49) have provided evidence for the synthesis of renin by vascular smooth muscle and endothelial cells in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…4 " 6 The presence of this local renin was also suggested by the production of angiotensin I (Ang I) by vessels perfused with tetradecapeptide renin substrate (TOP) 7 -8 and by the increased resistance of isolated muscle preparations when perfused with TDP. 9 -12 As regards angiotensinogen, its local production was suggested by its presence in vascular tissue 13 and by the presence of angiotensinogen mRNA in different tis-- 14 More recently, local production of angiotensinogen has also been demonstrated in isolated perfused beating heart. 15 Although a large body of data has been acquired for the different components of the local RAS in isolated large arteries and in cultured vascular cells, as well as by whole-organ perfusion, very little is known about the characteristics of this system in the microvascular network.…”
Section: Eric Vicaut and Xin Houmentioning
confidence: 99%
“…6). It has been reported that the inhibitory action on vascular ACE activity is prolonged by repeated adminis tration of ACE inhibitors (15,23,24). Vascular tissue contains the components necessary to generate A-II locally (15,25,26), and it is known that local vascular formation of A-ll is elevated in SHR (26) and 2K, 1 C-RHR (27).…”
Section: Antihypertensive Action In Shrmentioning
confidence: 99%